2020
DOI: 10.1371/journal.pgen.1008685
|View full text |Cite
|
Sign up to set email alerts
|

pH-dependent activation of cytokinesis modulates Escherichia coli cell size

Abstract: Cell size is a complex trait, derived from both genetic and environmental factors. Environmental determinants of bacterial cell size identified to date primarily target assembly of cytosolic components of the cell division machinery. Whether certain environmental cues also impact cell size through changes in the assembly or activity of extracytoplasmic division proteins remains an open question. Here, we identify extracellular pH as a modulator of cell division and a significant determinant of cell size across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 92 publications
3
19
0
Order By: Relevance
“…Our present work adds E. coli AmiB, AmiC, and the three LytM‐domain amidase activators to a growing list of pH‐sensitive PG enzymes and regulators (Castanheira et al., 2017, 2020; Mueller et al., 2019, 2020; Peters et al., 2016; Rico‐Pérez et al., 2015; Ursinus & Höltje, 1994; Vandal et al., 2008; Wang et al., 2019). Remarkably, Although E. coli PG composition remains nearly unchanged during growth in different pH environments (Peters et al., 2016), pH “specialist” enzymes are present in every major category of its cell wall autolysins (Mueller et al., 2019; Peters et al., 2016; Straaten et al., 2005).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our present work adds E. coli AmiB, AmiC, and the three LytM‐domain amidase activators to a growing list of pH‐sensitive PG enzymes and regulators (Castanheira et al., 2017, 2020; Mueller et al., 2019, 2020; Peters et al., 2016; Rico‐Pérez et al., 2015; Ursinus & Höltje, 1994; Vandal et al., 2008; Wang et al., 2019). Remarkably, Although E. coli PG composition remains nearly unchanged during growth in different pH environments (Peters et al., 2016), pH “specialist” enzymes are present in every major category of its cell wall autolysins (Mueller et al., 2019; Peters et al., 2016; Straaten et al., 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with a role for the cell division apparatus in the stimulation of amidase activity, we recently demonstrated that acidic pH promotes activation of cytokinesis in E. coli . Specifically, the cell division protein “triggers” FtsN hyperaccumulates at midcell during growth at low pH and stimulates cytokinesis at a reduced cell volume in this condition (Mueller et al., 2020). It is tempting to speculate hyperactivation of division at low pH increases the stimulatory capacity of the LytM activators.…”
Section: Discussionmentioning
confidence: 99%
“…Cells tolerate depletion—and even complete loss—of FtsK in acidic medium, a condition which corresponds with enrichment of FtsN at the cytokinetic ring. In accordance with the critical function for FtsN at low pH, it cannot be depleted in acidic medium ( 80 ), even in genetic backgrounds which permit extensive depletion at neutral pH ( 84 86 ).…”
Section: Responses To Environmental Threatsmentioning
confidence: 86%
“…(i) Condition-dependent modulatory proteins in E. coli. Significant genetic data from many groups indicate that division proteins FtsEX, ZipA, FtsK, FtsN, FtsP, and DedD all share partially overlapping roles in stabilizing, and potentially activating, septal PG synthesis in E. coli (75)(76)(77)(78)(79)(80). While many of these proteins promote efficient division across culture conditions, several are strictly required for viability only during growth in particular environmental conditions.…”
Section: Responses To Environmental Threatsmentioning
confidence: 99%
“…Microbes must frequently adapt to shifting environmental conditions, including pH. One feature of the bacterial response to pH is reorganization and altered biosynthesis of peptidoglycan (PG), the muropeptide polymer located outside the bacterial membrane that constitutes the bacterial cell wall and maintains cell shape integrity ( 13 ). However, the enzymes and transporters underlying these processes, especially at alkaline pH, are not well-defined.…”
Section: Main Textmentioning
confidence: 99%